A Simple Initiative to Decrease Time to Antibiotic Prophylaxis for Open Fractures Is Durable After 2 Years. Issue 18 (15th September 2021) - Goodman, Avi D.; Modest, Jacob M.; Johnson, Joey P.; Hayda, Roman A.
Abstract : Introduction: A simple antibiotic prophylaxis initiative can effectively decrease the time to antibiotic administration for patients with open fractures. We aim to determine whether adherence to the protocol decreased over time without active input from the orthopaedic trauma team. Patients and Methods: This retrospective cohort study included adult patients with open fractures (excluding hand) presenting directly to the emergency department at one Level I trauma center. Three separate 50-patient groups were included: a preimplementation cohort, immediately postimplementation cohort, and a retention cohort 2 years later. The primary outcome was time from emergency department presentation to antibiotic administration, and secondary outcomes were the percentage of patients receiving antibiotics within 60 minutes and incidence of infection requiring revision surgery within 90 days. The χ 2 and Student t -tests evaluated between-group differences, and multivariable linear or logistic regression evaluated risk factors. Results: After implementation, the time from presentation to antibiotic administration decreased markedly from 123.1 to 35.7 minutes and remained durable (50.0 minutes) at retention. The proportion of patients receiving antibiotics within 60 minutes increased markedly from 46% preimplementation to 82% postintervention and remained similar at retention (80%). The postintervention and retention groups were markedly more likely to receive antibiotics within 60 minutes than the preintervention group (odds ratio [OR], 8.4 and 4.7, respectively), as were patients with a higher Gustilo-Anderson type (OR, 2.4/unit increase), lower extremity injury (OR, 2.8), and male sex (OR, 3.1); mechanism, age, and Injury Severity Score were not associated. No difference was observed in infection. Conclusions: Our educational initiative showed durable results in reducing the time from presentation to antibiotic administration after 2 years. Level of Evidence: Therapeutic Level III